Monitoring of education for sustainable development in Germany – insights from early childhood education, school and higher education. Issue 4 (3rd April 2019) - Singer-Brodowski, Mandy; Brock, Antje; Etzkorn, Nadine; Otte, Insa
Abstract: In Germany, the implementation of the UNESCO Global Action Programme (GAP) on Education for sustainable development (ESD) 2015–2019 aims to implement ESD more profoundly within the structures of Germany's educational system. In this context, a national monitoring has been set up in order to analyze the extent and quality of ESD implementation in all educational areas. The paper contains the results of an indicator-based desk research comprising a content analysis of key documents in three areas of education: early childhood education, school education and higher education over a period of 5 years (2011–2016). Overall, the main results indicate that, at the level of key documents, the goal of a broad implementation of ESD is not yet achieved, while there are considerable differences among the federal states. ESD and related concepts can be found more frequently particularly in documents that are more recent. At the same time, ESD is increasingly predominating other educational concepts such as environmental education. The results are one component of a comprehensive monitoring process of ESD-implementation on the level of documents and offer important insights relevant for further (political) activities aiming at a mainstreaming of ESD.